The European Union's Credibility and Treatment of Refugees - Nasrallah, Wissam Hussein (2024)
In today’s world, it is important to understand how different factors might influence the treatment of refugees, especially since the “1948 Universal Declaration of Human Rights” which clearly mentions the right to seek protection in other countries when their home country is dangerous to reside in. Therefore, this thesis aims to study refugee treatment in EU countries, with the purpose of understanding how the EU’s political and strategic interests in the home states of refugees and in maintaining relations with key players, the perception of the religion and ethnicity of different refugees, and the impact of media on shaping the opinion regarding refugees and the threat associated with their entry to the destination country can all impact refugee treatment. The present literature on the topic explores the way the European union handled asylum and immigration cases. Furthermore, it offers a detailed examination of the EU’s refugee policies and sociopolitical processes. It has been concluded that the EU’s refugee policy is deeply influenced by the interests and authority of individual member states, which has caused a fragmentation in the EU’s refugee policy, where different EU countries would handle the refugee situation based on their own gain. Additionally, it has been shown that public opinion and perception of refugees are mainly influenced by their ethnicity, religion, and how media outlets portray them. The latter significantly influences the way refugees are treated and may pose multiple questions regarding the degree to which human rights are respected in EU member states, which claim to uphold human rights principles. The sociological phenomena that are hypothesized to influence the treatment of refugees in EU countries are explained through several theoretical frameworks, such as “the Social Identity Theory” and the “Intergroup Perceived Threat" theory. In addition to offering insight to scholars about how various factors might influence refugee treatment, and how this might affect humanity in general, the thesis calls for coordinated initiatives at the European and international levels to fill the gaps and promote more inclusive refugee policies based on human rights and justice. To sum up, the thesis adds to the current knowledge and present body of literature on migration, geopolitics, and human rights all while supporting the conduction of future research delving more deeply into this topic.